PERUBAHAN TEKSTUR KERUPUK UDANG MENGGUNAKAN PASIR KALI DAN PASIR GUNUNG SEBAGAI MEDIA PENGHANTAR PANAS PADA PROSES PENYANGRAIAN - Sudirman Rachim; Jamaluddin Jamaluddin; Kadirman Kadirman (Universitas Negeri Makassar, 2019)
The texture of the food consists of smooth and rough, liquid and solid, hard and soft. Texture greatly affects the image or taste of food that can be felt with pressure and movement of receptors in the mouth. One of the types of food that depends on texture is crackers. The purpose of this study was to determine the changes in texture of crackers using sand kali and mountain sand as heat conductive media for roasting by using temperatures of 120 OC, 140 OC and 160 OC and various variations of time ie 10, 15, 20 and 25 seconds. The parameters measured are the value of cracker hardness and cracker water content. The results showed that river sand kali and mountain sand can change the texture of crackers through roasting, because of the heat transfer from the heating wall in the sand so that it affects the moisture content and starch content in roasted crackers, in the roasting process, the temperature affects the texture of the crackers produced where good temperature id use is 140 OC for kali sand times and 160 OC for mountain sand with a time of 20 and 25 seconds.